2013
DOI: 10.1177/2167479512472883
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on Communication and Sport

Abstract: In this essay, Toni Bruce considers key cultural and social issues at play in the relationship between mediated sport and women. The treatment reflects on over 30 years of research and assesses not only central tendencies and changes in the way media covers women's sporting events and achievements but also considers how this coverage interplays with women's sense of their place in and relationship to sport. The essay opens with core arguments about the cultural importance of the communication and sport intermi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 32 publications
1
74
0
2
Order By: Relevance
“…Not only does so-called 'media sport', that is sport represented through media rather than where it happens, produce coverage by men, but it is also produced 'for men and about men' (Bruce, 2013: 128). Chambers et al agree, arguing that sports news 'is home to one of the most intense and most historically enduring gender divisions in journalism, in terms of who is permitted to cover which sports as journalists, how athletes are covered, as well as in terms of which genders are served as audiences ' (2004: 98).…”
Section: Women In Sports Journalismmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only does so-called 'media sport', that is sport represented through media rather than where it happens, produce coverage by men, but it is also produced 'for men and about men' (Bruce, 2013: 128). Chambers et al agree, arguing that sports news 'is home to one of the most intense and most historically enduring gender divisions in journalism, in terms of who is permitted to cover which sports as journalists, how athletes are covered, as well as in terms of which genders are served as audiences ' (2004: 98).…”
Section: Women In Sports Journalismmentioning
confidence: 99%
“…Already during the Edwardian era the press was highly successful when 'tapping into the nation's captivation with sport', and the number of stories devoted to sports and sport culture in both traditional mainstream media and new internet-based options such as blogs and tweets have since steadily increased (Bruce, 2013;Boyle and Haynes, 2009: 23-24).…”
Section: Introductionmentioning
confidence: 99%
“…Reiterating the earlier argument by Bruce (2013), white males are most ideally suited to take up the ideal subject position and read the text according to its preferred reading (Hall 1980). Marginalized groups may instead more often opt to utilize an oppositional or negotiated reading whereby they either reject the dominant discourse or find some middle ground that incorporates both preferred and oppositional elements (Hall 1980).…”
Section: A Cultural Studies Approachmentioning
confidence: 99%
“…Although improvements have been visible, sportswomen (especially those performing in sports that are traditionally geared towards men) remain underrepresented in terms of media coverage when compared to sportsmen (Adams et al 2014). Furthermore, women are often represented in stereotypical ways that trivialize and marginalize their athletic performances and instead focus on their femininity and heterosexuality (Bruce 2013;Pressland 2012). Research has also shown that sport and football commentators (unconsciously) employ racial/ethnic stereotypes (Hylton 2009;McCarthy, Jones, and Potrac 2003), thereby reinforcing long-standing ideas about the natural athletic black body and white cognitive capabilities (Carrington and McDonald 2001).…”
Section: Introduction and Aimmentioning
confidence: 99%
See 1 more Smart Citation